2017
DOI: 10.1002/14651858.cd009013.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Information and communication technologies (ICT) for promoting sexual and reproductive health (SRH) and preventing HIV infection in adolescents and young adults

Abstract: Information and communication technologies (ICT) for promoting sexual and reproductive health (SRH) and preventing HIV infection in adolescents and young adults (Protocol)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Mobile health, or mHealth, is defined as "a medical and public health practise supported by mobile phones, tablets, patient monitoring devices, personal digital assistants (PDAs), and other wireless devices" [10]. A study conducted revealed that a technology-based intervention with adolescents and young adults to improve access to SRH information had an impact on condom use, abstinence, and increased knowledge of STIs and pregnancy among users [11]. Importantly, mHealth interventions have the potential to offer adolescents accurate and non-judgmental SRH information and services [12].…”
Section: Introductionmentioning
confidence: 99%
“…Mobile health, or mHealth, is defined as "a medical and public health practise supported by mobile phones, tablets, patient monitoring devices, personal digital assistants (PDAs), and other wireless devices" [10]. A study conducted revealed that a technology-based intervention with adolescents and young adults to improve access to SRH information had an impact on condom use, abstinence, and increased knowledge of STIs and pregnancy among users [11]. Importantly, mHealth interventions have the potential to offer adolescents accurate and non-judgmental SRH information and services [12].…”
Section: Introductionmentioning
confidence: 99%